Magnetic interactions and spin-reversal mechanism in ErMn1-xCoxO3-delta samples - Morilla-Santos, C. [UNESP]; Arruda, L. B. [UNESP]; Silva, C. A. [UNESP]; Lisboa Filho, Paulo Noronha [UNESP] (Springer, 2011)
Manganese-based oxides present a very complex magnetic phase diagram, and many of their basic physical properties and magnetic interaction need more exploration. At the crystallographic level, the magnetic properties of rare-earth oxide manganites are strongly affected by changes in the rare-earth ion present in the structure, the nature of the transition metals, and the possibility of electronic valence fluctuations. This work studied the synthesis procedure and structural and magnetic characterization of high-quality polycrystalline samples of the ErMn1-xCoxO3-delta family. Crystallographic analyses show a decrease in lattice parameters as cobalt substitution increases, accompanied by a reduction in the interatomic distances and a small increase in MT-O-MT angles (MT= cobalt and manganese) considering the c-axis. Magnetic measurements indicated a phase separation picture, and show the coexistence of different magnetic interactions with the samples considering the Mn/Co ratio. In addition, the spin-inversion mechanism is interpreted as having a crucial role in the family's magnetic response.
Keywords: Sol-gel processes; Magnetic properties; Perovskites; Transition metal oxides